2017
DOI: 10.1364/oe.25.012896
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced ultrafast infrared spectroscopy using coupled nanoantenna arrays

Abstract: Surface-enhanced nonlinear vibrational spectroscopy using periodic gold nanoantenna arrays is demonstrated. The dipolar coupling among arrayed nanoantennas is shown to have striking impact on near-field enhancements of femtosecond pulsed-fields and on nonlinear signal enhancements. The condition near the collective-resonance achieves averaged signal enhancement of 850 times and local signal enhancement of 1.8 × 10 times, substantially reducing the required pump energy from micro-joule to nano-joule level. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…In the traditional linear SEIRA experiments, the signal scales as a second power of the enhanced electric field . In order to get more insight into the mechanism of plasmon–molecule interaction, we use third-order nonlinear spectroscopy, where the signal scales as the fourth power of the field. Combining the results of linear absorption, third-order femtosecond transient absorption, two-dimensional infrared heterodyned spectroscopy (2DIR), and theoretical analysis, we show that even though locally the plasmon fields are appreciably enhanced, the strength of the near-field coupling is not sufficient to explain the magnitude of the experimentally observed signals in samples with thick polymer films, which we found is caused by the radiation damping interaction. ,, Consequently, we identified that the surface-enhanced signal in samples with a film thickness of only a few nanometers can be dominated by the radiation damping mechanism, especially when strong vibrational chromophores are involved.…”
mentioning
confidence: 99%
“…In the traditional linear SEIRA experiments, the signal scales as a second power of the enhanced electric field . In order to get more insight into the mechanism of plasmon–molecule interaction, we use third-order nonlinear spectroscopy, where the signal scales as the fourth power of the field. Combining the results of linear absorption, third-order femtosecond transient absorption, two-dimensional infrared heterodyned spectroscopy (2DIR), and theoretical analysis, we show that even though locally the plasmon fields are appreciably enhanced, the strength of the near-field coupling is not sufficient to explain the magnitude of the experimentally observed signals in samples with thick polymer films, which we found is caused by the radiation damping interaction. ,, Consequently, we identified that the surface-enhanced signal in samples with a film thickness of only a few nanometers can be dominated by the radiation damping mechanism, especially when strong vibrational chromophores are involved.…”
mentioning
confidence: 99%
“…41 In the case of the antenna arrays, additional control over the resonant wavelength can be achieved by tuning the strength of the near-neighbor interaction in the antenna axis (longitudinal) direction. 51,52,54 Stronger coupling, obtained for shorter distances between the adjacent antennas (a smaller longitudinal period of the array, Λ l ), red-shifts the wavelength of the resulting "pseudo-local" resonance, λ ̃loc .…”
mentioning
confidence: 99%
“…Because of strong light–matter coupling, SPhPs exhibit a reduced phase and group velocities and, therefore, bring about a subwavelength localization and an electric-field enhancement, respectively. These properties make SPhPs promising for nanophotonic applications in the mid-IR range, such as surface-enhanced spectroscopy, thermal radiation control, , and strong-field phenomena. , To date, the linear properties of SPhPs, namely, the dispersion relation, have been intensively studied. …”
mentioning
confidence: 99%